A Non-Muslim President in a Muslim State: Islamic Political Discourse in Contemporary Indonesia - Mujar Ibnu Syarif (Universitas Islam Negeri Jakarta, 2012)
Abstrak: Presiden Non-Muslim di Negara Muslim: Diskursus Politik Islam dalam Konteks Politik Indonesia Kontemporer. Artikel ini secara spesifik dimaksudkan untuk membahas secara kritis pendapat para cendekiawan Muslim Indonesia tentang kemungkinan non-Muslim menjadi presiden di Negara Republik Indonesia yang merupakan negara berpenduduk Muslim terbesar di dunia. Hingga detik ini, wacana Islam klasik tentang masalah ini cenderung terjebak dalam model analisis normatif yang terkesan rigid dan tidak toleran. Wacana ini, sampai batas tertentu, kurang dapat menghargai kondisi sosial, budaya, sejarah, dan kompleksitas politik masyarakat Muslim. Oleh karena itu, diskursus klasik mengenai masalah ini oleh banyak cendekiawan Indonesia kontemporer dipandang telah gagal merespons dinamika sosial-politik saat ini, terutama bila dilihat dari sudut pandang multi-kulturalisme dan demokrasi. Artikel ini membahas dimensi penting mengenai kepemimpinan non-Muslim di Indonesia yang sering dilupakan atau sangat jarang didiskusikan.Kata Kunci: Islam di Indonesia, Presiden Non-Muslim, Otoritas Tuhan, Piagam Jakarta.Abstract: A Non-Muslim President in a Muslim State: Islamic Political Discourse in Contemporary Indonesia. This article charts the political discourse amongst Islamic leaders regarding the possibility of a non-Muslim becoming President in Indonesia, the world’s most populated Muslim state, an important issue but one that is only seldom discussed in an academic context. Until recently, classical Islamic discourse on this issue, which has generally rejected this possibility, had tended to be trapped in a normative model of analysis which today seems intolerant and rigid. This article contends that this discourse, to some extent, does not properly appreciate the complex social, cultural, historical and political realities of the Muslim community today. Indeed, many other contemporary scholars view this mode of discourse as failing to respond to the current social-political dynamic, especially those scholars coming at it from a multicultural democratic perspective. Perhaps most importantly, the legal reality—even though there is a reasonable degree of controversy surrounding it—which is that there is no criterion that the President has to be Muslim, is also rejected by this discourse.Keywords: Islam in Indonesia, Non-Muslim President, God’s Authority, Jakarta CharterDOI: 10.15408/ajis.v12i1.971